'INEFFECTIVE SPONTANEOUS VENTILATION (00033)' NURSING DIAGNOSIS: A REVISION STUDY. - Virginia Fazi; Gian Domenico Giusti; Rosaria Cozzolino; Nicola Ramacciati (Milano University Press, 2024)
Background: Spontaneous ventilation, essential for human life, is addressed by the nursing diagnosis "Ineffective Spontaneous Ventilation" which requires strong scientific support. Aim: This revision study aimed to elevate this nursing diagnosis to a higher level of evidence by clarifying its definition, clinical indicators, and differentiation from other diagnoses. The diagnosis is crucial for identifying patients with compromised breathing who may require respiratory support. Methods: Researchers searched the PubMed medical literature database for studies (2006-2021) on the "Ineffective Spontaneous Ventilation" diagnosis. Results: The search identified 45 studies, but after applying pre-defined criteria, only 10 articles were included in the final analysis. These articles mainly focused on the accuracy of defining characteristics for the diagnosis. Despite limitations of individual defining characteristics, Impaired Spontaneous Ventilation remains a valuable nursing diagnosis for patients with respiratory issues. Utilizing clusters of these characteristics and considering the specific context can significantly enhance the accuracy of ISV diagnosis. Conclusion: The findings unequivocally corroborate the definition of Impaired Spontaneous Ventilation, with eight out of ten articles providing validation. Moreover, the analysis proposes additional defining characteristics, namely dyspnea and cyanosis, to further refine the diagnosis. The clinical applicability of Impaired Spontaneous Ventilation extends to a wide range of patient populations and conditions. It serves as a critical marker for premature infants grappling with respiratory and cardiac challenges, trauma victims battling life-threatening injuries, and patients relying on mechanical ventilation in intensive care settings.